Perception of pregnant women and postpartum women of factors related to breastfeeding abandonment - Salles, Kyane Victória; Caino, Mara Marchiori Marchiori; Frigo, Leticia Fernandez; Vieira, Sylvio André; Costenaro, Regina Gema (Disciplinarum Scientia | Saúde, 2024)
Objective: to understand the perception of pregnant and postpartum women regarding the abandonment of early maternal pregnancies. Method: qualitative research, exploratory and descriptive approach, carried out between January and May 2022, in a Basic Health Unit in the state of Rio Grande do Sul. The participants were four pregnant women and 12 postpartum women. A semi-structured form was used with questions related to abandonment of maternal care. The data is analyzed based on the content analysis proposed by Bardin (2016). Results: The organized and analyzed data will result in two thematic categories: “Nipple fissures”; and “Insufficient guidance on maternal support during prenatal care”. At this moment, it is essential to value the meaning that women attribute to this experience and direct the health actions of the mother-child binomial. Final Considerations: We highlight the importance of raising and consolidating indicators to support effective policies and practices for promoting maternal rights and controlling the main associated factors.